2011
DOI: 10.1523/jneurosci.3159-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

PKA/AKAP1 and PP2A/Bβ2 Regulate Neuronal Morphogenesis via Drp1 Phosphorylation and Mitochondrial Bioenergetics

Abstract: Mitochondrial shape is determined by fission and fusion reactions, perturbation of which can contribute to neuronal injury and disease. Mitochondrial fission is catalyzed by dynamin-related protein 1 (Drp1), a large GTPase of the dynamin family that is highly expressed in neurons and regulated by various posttranslational modifications, including phosphorylation. We report here that reversible phosphorylation of Drp1 at a conserved Ser residue by an outer mitochondrial kinase (PKA/AKAP1) and phosphatase (PP2A/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
172
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(195 citation statements)
references
References 66 publications
11
172
1
Order By: Relevance
“…1), consistent with the report that DAP3 is a component of the mitochondrial ribosomal small subunit (31). In addition, we show that knockdown of DAP3 leads to mitochondrial protein synthesis defects and mitochondrial dissipation, which may alter the antagonistic activities of PKA and calcineurin on mitochondria (41,43), resulting in the dephosphorylation of Drp1 at Ser-637 and mitochondrial fragmentation. It has been reported that ectopic overexpression of DAP3 caused mitochondrial fragmentation (33).…”
Section: Discussionsupporting
confidence: 91%
“…1), consistent with the report that DAP3 is a component of the mitochondrial ribosomal small subunit (31). In addition, we show that knockdown of DAP3 leads to mitochondrial protein synthesis defects and mitochondrial dissipation, which may alter the antagonistic activities of PKA and calcineurin on mitochondria (41,43), resulting in the dephosphorylation of Drp1 at Ser-637 and mitochondrial fragmentation. It has been reported that ectopic overexpression of DAP3 caused mitochondrial fragmentation (33).…”
Section: Discussionsupporting
confidence: 91%
“…Also, Drp1-dependent mitochondrial fission is necessary for dendritic localization of mitochondria (Fig. 5), as well as spine formation and synaptogenesis in hippocampal cultures (Li et al, 2004;Dickey and Strack, 2011). Ca 2+ uptake by postsynaptic mitochondria has been shown to be necessary for long-term potentiation (LTP) of nociceptive inputs to the spinal cord (Fig.…”
Section: Mitochondrial Dynamics In Synaptic Transmission and Plasticitymentioning
confidence: 99%
“…Given the importance of processes, such as ATP production, Ca 2+ transients, neurotransmitter metabolism and ROS signaling, in synaptic transmission it is not surprising that recent work has illustrated that perturbations in mitochondrial physiology exert profound effects on neuronal development and function. Mitochondrial ATP production, Ca 2+ buffering, neurotransmitter metabolism and ROS signaling themselves are spatially and temporally regulated in neurons through mitochondrial localization (Brodin et al, 1999;Jayashankar and Rafelski, 2014;Li et al, 2004;Niescier et al, 2013;Rueda et al, 2014;Sheng, 2014;Vos et al, 2010), mitochondrial bioenergetics (Rueda et al, 2014;Dickey and Strack, 2011), and mitochondrial biogenesis (Cheng et al, 2012), all of which are strongly influenced by mitochondrial dynamics, which entails mitochondrial fission, fusion and transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial shape influences rates of respiration (1)(2)(3)(4), calcium homeostasis (5-7), and transport of the organelle especially in highly polarized cells such as neurons (8). In addition, mitochondrial fission contributes to efficient cellular execution by apoptosis (9).…”
mentioning
confidence: 99%